Holographic Near-Eye 3D Display Method Based on Large-Size Hologram - Liu, Su-Juan; Ma, Ning-Tao; Li, Ping-Ping; Wang, Di (Frontiers in Materials, 2021)
In this paper, we propose a holographic near-eye 3D display method based on large-size computer-generated hologram (CGH). The reconstructed image with a large viewing angle is obtained by using a time multiplexing and spatial tiling system. The large-size CGHs are generated and they record the information of the 3D object from different angles. The CGHs are reproduced at different moments. For a certain reconstructed moment, three spatial light modulators (SLMs) spatially spliced into a linear structure are used to load a single CGH. The diffraction boundary angle of the reconstructed light forming each image point is equal to the maximum diffraction angle of the SLM, so the viewing angle of the image generated by the CGH is enlarged. For different CGHs, the incident angle of reconstructed light is changed. Through time multiplexing, the reconstructed images of the CGHs are combined into a reconstructed image whose viewing angle is further enlarged. Due to the large viewing angle of the reconstructed image, the proposed method has unique advantages in near-eye display. The feasibility of the proposed method is proved by experimental results.